(untitled) (Iraqi Journal of Medical Sciences, 2018)
Background: Human respiratory syncytial virus (hRSV) is a major cause of viral lower respiratory tract infection among infants and young children less than 2 years old. Multiple methods are used for the laboratory diagnosis of hRSV infections, including chromatographic immunoassay, enzyme linked immunosorbent assay (ELISA) and reverse transcription polymerase chain reaction (RT-PCR) technique for detection hRSV-antigens, hRSV-antibodies and hRSV-RNA, respectively. Objective: To compare the efficiency of three diagnostic methods in detection of hRSV in infants and young children with chest infection. Methods: This study included 100 hospitalized infants and young children (39 females and 61 males) aged from (1) month to (24) months, their mean age (6.87 ± 6.03) months, who required hospital admission at the Pediatric Department in Al-Imamein AL-Kadhimein Medical City Hospital, Central Teaching Pediatric Hospital, and Al-Kadhimiya Pediatric Hospital in Baghdad-Iraq. Samples were collected over a three-month winter period from January 2017 to April 2017. Fresh nasal swab specimens were collected and testes for hRSV antigens by using chromatographic immunoassay as a rapid test, in addition, nasopharyngeal/throat swabs specimens were processed for detection of hRSV-RNA by RT-PCR, both for direct detection. Also, ELISA was done to measure anti-hRSV IgM antibodies in serum for indirect detection of RSV infection. Results: hRSV was found to be positive in (27%), (56%) and (44%) of specimens by rapid chromatographic immunoassay, ELISA and RT-PCR technique, respectively. Comparing with RT-PCR, the sensitivity of rapid test was (59.09%) ranged from (44.41) to (72.31) and the specificity was (98.21%) ranged from (90.55) to (99.91) with likelihood ratio equal to (33.09), while the sensitivity of ELISA test was (75.61%) ranged from (60.66) to (86.17) and specificity was (59.62%) ranged from (46.07) to (71.84) with likelihood ratio equals to (1.87). Conclusion: The RT-PCR technique was more sensitive than antigen or antibody detection methods for the diagnosis of hRSV Keywords: hRSV, rapid chromatographic immunoassay, ELISA, RT-PCR Citation: Al-Shuwaikh AMA, Ali SH, Arif HS. Detection of respiratory syncytial virus in infants and young children with chest infection: a comparison of reverse transcription-PCR technique to chromatographic immunoassay and enzyme linked immunosorbent assay. Iraqi JMS. 2018; 16(3): 319-326. doi: 10.22578/IJMS.16.3.11